Customer Relationship Management (CRM) in Health Care Industry - A Study of Select Corporate Hospitals in Vijayawada, Andhra Pradesh - Narasimha Rao, V.; Siva Prasad, A. V. V. (Indian Journal of Marketing, 2011)
Customer Relationship Management (CRM) is perhaps the most important concept of modern marketing. Until recently, CRM has been defined narrowly as a customer data management activity. In its broader sense, CRM is the overall process of building and maintaining profitable customer relationships by delivering superior customer value and satisfaction. It deals with all aspects of acquiring, keeping and growing customers. The key to building lasting customer relationships is to create superior customer value and satisfaction. Organizations can build customer relationships at many levels, depending on the nature of the target market. To build customer relationships, companies can add structural ties as well as financial and social benefits. Today's companies are building more direct and lasting relationships with more carefully selected customers. Changing demographics, more sophisticated competitors mean that there are fewer customers to go around. Many organizations are now fighting for shares of flat or fading markets. In addition to being good at customer relationship management, marketers must also be good at partner relationship management, which means working closely with partners in other company departments and outside the company to jointly bring greater value to customers. Thus, the goal of marketing is to build and manage profitable customer relationships. Successful CRM focuses on the profiling or understanding the needs and desires of the customers and is achieved by placing these needs at the heart of the business by integrating them with the organization's strategy, people, and technology and business processes. CRM requires a synergistic integration of the strategy, people and technology of an organization. This integration leads to the creation of the service process that seeks to develop an ongoing relationship with customers and results in the creation of an exchange relationship that is mutually beneficial for both the organization and the customer. CRM must come from the top. It is an all-encompassing strategy, and no one department or Call center or Information Technology manager can drive the cross-functional process changes required. Thus, CRM is a Holistic approach.